Clamor Schürmann's Barngarla grammar: A commentary on the first section of A vocabulary of the Parnkalla language - Clendon, Mark (University of Adelaide Press, 2015)
The work of the German missionaries on South Australian languages in the first half of the nineteenth century has few contemporary parallels for thoroughness and clarity. This commentary on the grammatical introduction to Pastor Clamor Schürmann's Vocabulary of the Parnkalla language of 1844 reconstructs a significant amount of Barngarla morphology, phonology and syntax. It should be seen as one of a number of starting points for language-reclamation endeavours in Barngarla, designed primarily for educators and other people who may wish to re-present its interpretations in ways more accessible to non-linguists, and more suited to pedagogical practice.